GR_GERICHTE ZF 2004 33 vom 9. November 2004 , Zivilrecht anderes Bundesgesetz - GR Gerichte (2004)
Forderung (negative Feststellungsklage) | OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc. (OR 394-529)